Construct Validation of a Critical Thinking Disposition Instrument for Physics Education Students: An Exploratory and Confirmatory Factor Analysis Approach - Verawati, Ni Nyoman Sri Putu; Rokhmat, Joni; Harjono, Ahmad; Makhrus, Muh (Universitas Pendidikan Mandalika, 2026)
This study examined the construct validity of a critical thinking disposition instrument for Physics Education students using an Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) approach. The instrument measured four dimensions of critical thinking disposition, namely open-mindedness, truth-seeking, analyticity, and inquisitiveness, represented by 16 observed indicators. The study involved 250 undergraduate students enrolled in Physics Education programs from 10 public and private universities in Indonesia. Descriptive analysis showed that the mean score of each dimension was 3.00, with standard deviations ranging from 1.07 to 1.10 and Cronbach’s alpha values between 0.745 and 0.784. The data met the requirements for factor analysis, as indicated by a Kaiser-Meyer-Olkin value of 0.863, a significant Bartlett’s Test of Sphericity (χ² = 1247.060, p < .001), and a total reliability coefficient of 0.858. EFA identified a four-factor structure explaining 60.20% of the total variance. CFA further confirmed the adequacy of the measurement model, with all standardized factor loadings exceeding 0.70, composite reliability ranging from 0.847 to 0.857, and average variance extracted ranging from 0.580 to 0.600. These findings indicate that the instrument demonstrates satisfactory construct validity and reliability and is suitable for measuring critical thinking disposition among Physics Education students.